The Brown and Levinson theory revisited: A statistical analysis. (July 2017) - Song, Sooho
Abstract: The Brown and Levinson (1987) theory posits that the combination of social distance, power ratio, and task imposition determine politeness weightiness perception regardless of the culture. In order to test the effects of culture, I conducted statistical analyses using subjects with American, East Asian, and Latin American cultural backgrounds. The results reveal that task imposition does not have a statistically significant impact on the speaker's determination of politeness weightiness in East Asia while it does in the US and Latin America.